Liquid biopsy: value for melanoma therapy? - Buder-Bakhaya, Kristina; Machiraju, Devayani; Hassel, Jessica C. (Oncology research and treatment, 2017)
Treatment of metastatic melanoma has undergone tremendous changes over the past few years. There are now highly effective systemic therapies available: targeted therapy with BRAF and MEK inhibitors in BRAF-V600-mutant melanoma and immunotherapies, including PD-1 antibodies with or without CTLA-4 antibody, that can be used regardless of mutational status. However, long-term tumor control is only achieved in a minority of patients. Liquid biopsy using circulating tumor cells, circulating tumor DNA (ctDNA), circulating mRNA and micro-RNA might represent valuable biomarkers, e.g. in the setting of systemic treatment for metastatic melanoma. Pre-treatment detection of BRAF V600-mutant ctDNA has been shown to be a prognostic factor in patients receiving BRAF/MEK inhibitor treatment. Furthermore, monitoring of ctDNA of known driver mutations can be used for treatment monitoring and detection of acquired resistance. However, results of the currently available studies need to be interpreted with caution as multiple approaches were used that are hardly comparable. So far, even with advancement of methods, there are only prognostic but no predictive biomarkers available.